Dazzling Descriptions and Tantalizing Titles: How Simple Versus Complex Course Information Influences Course Selection. (April 2022) - Mourey, James A.; Markley, Melissa M.; Koernig, Stephen K.
Research exploring a student's "path to purchase" when considering course selection has revealed a number of influential factors including course content, reputation, and professor style. To date, little is known about the direct (or indirect) influence that course titles and course descriptions have on student interest and enrollment in courses, or how easy-sounding (simple) versus difficult-sounding (complex) information is inferred and interpreted as it relates to various enrollment markers. Using ideas from metacognition research, this research explores the impact of subjective assessment of simple versus complex course titles and course descriptions on general interest in a course and enrollment intentions. Findings indicate that not only does an easy versus complex course description affect enrollment intention, but it also affects subjective interpretations of course interest, expected workload, and learning outcomes, whereas course title has few meaningful effects. Application of these ideas for specific students and future research opportunities are discussed.